The myth of equal opportunity in Germany? - Valentina S. Consiglio; Denisa M. Sologon (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
Providing equal opportunities to all members of society independent of an individual's socioeconomic background is a major objective of German policy makers. However, evidence on the access to education suggests that opportunities of children with a non-academic family background are still unequally obstructed. When analysing the labour market implications of this disadvantage in human capital, social capital as an additional source of inequality often lacks attention. Drawing on the instrumental value of rather loose contacts (i.e. weak ties) on the labour market as revealed by Mark Granovetter (1974), this research paper goes beyond the human capital approach and includes a measure of instrumental social capital in the form of weak-tie career support in the earnings function. We shed light on the structure of the wage gap between those with and without an academic family background and complement an Oaxaca- Blinder decomposition with quantile regressions to analyse potential capital and return deficits separately. We find that a significant part of the wage gap can be explained by deficits that those from less educated families incur with respect to human and instrumental social capital. While the capital deficit due to educational attainment is larger, a non-academic family background is further associated with a significant deficit in returns to instrumental social capital at some parts of the distribution. As this suggests inequalities of opportunity on the German labour market to occur along the lines of parental education even beyond the education system, it urges policy makers to consider designing equality measures that do the same.
Keywords: I24; J31; J62; 330; wage gap; (non-)academic family background; German labour market; Oaxaca-Blinder decomposition; quantile regression; human capital; instrumental social capital